7(-5-8x)=7x-7(4+8x)

Simple and best practice solution for 7(-5-8x)=7x-7(4+8x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(-5-8x)=7x-7(4+8x) equation:



7(-5-8x)=7x-7(4+8x)
We move all terms to the left:
7(-5-8x)-(7x-7(4+8x))=0
We add all the numbers together, and all the variables
7(-8x-5)-(7x-7(8x+4))=0
We multiply parentheses
-56x-(7x-7(8x+4))-35=0
We calculate terms in parentheses: -(7x-7(8x+4)), so:
7x-7(8x+4)
We multiply parentheses
7x-56x-28
We add all the numbers together, and all the variables
-49x-28
Back to the equation:
-(-49x-28)
We get rid of parentheses
-56x+49x+28-35=0
We add all the numbers together, and all the variables
-7x-7=0
We move all terms containing x to the left, all other terms to the right
-7x=7
x=7/-7
x=-1

See similar equations:

| (x+1)/2=x-9 | | 25y^4-25y+10=0 | | -3/4+z=3/1/2 | | 7r+8r=0 | | -3/4+z=31/2 | | 5x+8(3+5x)=-111 | | -25+5d=-100 | | 4k-16=0 | | -9c=-81 | | x=(1/4*2)+(1/4*8)+1/4(3+x)+1/4(5+x) | | x=4.5+x | | x=4.5+ | | (0.02-x)/x=0.85 | | 3x*x+12=42 | | 3t^2-22t+21=0 | | 2m+7=5 | | 8x-32=14x-(2x+70) | | (1+r)^6-8r-1=0 | | 2x+17=67−3x | | d/7-3=-5 | | L(3x-2)=9x-6 | | 6x+12^2=0 | | 1,5x-32=58 | | 6x+9=13/15-x | | (2x-3)^2-(3x^2-2)=(x+5)(x-5) | | W(3x-2)=9x-6 | | 4-3x=3+4+4(2x-3) | | 8m+6=56 | | 5y-8=31 | | 3v2+7v+4=0 | | 42x-(x)=86 | | 3770=1/2(58)h |

Equations solver categories